Competitive Transient Electrostatic Adsorption for In Situ Regeneration of Poisoned Catalyst. Issue 4 (1st February 2019) - Pan, Yanbo; Shen, Xiaochen; Yao, Libo; Bentalib, Abdulaziz; Yang, Jinlong; Zeng, Jie; Peng, Zhenmeng
Abstract: Catalyst deactivation by poisoning species is one important concern in catalysis processes and causes significant catalyst material and operation costs due to process shutdown and catalyst replacement. We report one new in situ catalyst regeneration method, which utilizes competitive electrostatic adsorption of charged ions which are generated with moderate DC voltage supply following the Townsend discharge mechanism to desorb poisoning species and the transient characteristic of electrostatically adsorbed ions to recover the active sites for catalysis. We demonstrate effectiveness of this new concept using HCOOH decomposition on Pt catalyst as model reaction and find the deactivated Pt regains the activity in presence of Ar + generation. DFT simulations and classical electrical discharge calculations show Ar + ions have significantly higher electrostatic adsorption energy than desorption energy of CO poisoning species that helps to desorb CO from Pt and generate more available active sites. This new in situ catalyst regeneration method, with convenient, noninvasive and low operation cost features, provides a promising strategy to overcome the challenges associated with current technologies that handle catalyst deactivation. Abstract : All charged up : We report one new in situ catalyst regeneration method, which utilizes competitive electrostatic adsorption of charged ions to desorb poisoning species and transient characteristic of these electrostatically adsorbed ions to recover the active sites for catalysis. The charged ions can be generated with moderate DC voltage supply following the Townsend discharge mechanism. Effectiveness of this new concept is demonstrated using HCOOH decomposition on Pt catalyst as model reaction.